Serum levels of anti-apolipoprotein A-1 auto-antibodies and myeloperoxidase as predictors of major adverse cardiovascular events after carotid endarterectomy - Vuilleumier, Nicolas; Montecucco, Fabrizio; Spinella, Giovanni; Pagano, Sabrina; Bertolotto, Maria; Pane, Bianca; Pende, Aldo; Galan, Katia; Roux-Lombard, Pascale; Combescure, Christophe; Dallegri, Franco; Mach, François; Palombo, Domenico (Thrombosis and Haemostasis, 2013)
We aimed at challenging the prognostic accuracies of myeloperoxidase (MPO) and antibodies anti-apolipoprotein A-1 (anti-apoA-1 IgG), alone or in combination, for major adverse cardiovascular events (MACE) prediction, one year after carotid endarterectomy (CEA). In this prospective single centre study, 178 patients undergoing elective CEA were included. Serum anti-apoA-1 IgG and MPO were assessed by enzyme-linked immunosorbent assay prior to the surgery. Post-hoc determination of the MPO cut-off was performed by receiver operating characteristics (ROC) analyses. MACE was defined by the occurrence of fatal or non-fatal acute coronary syndromes or stroke during one year follow-up. Prognostic accuracy of anti-apoA-1 IgG was assessed by ROC curve analyses, survival analyses and reclassification statistics. During follow-up, 5% (9/178) of patients presented a MACE, and 29% (52/178) were positive for anti-apoA-1 IgG. Patients with MACE had higher median MPO and anti-apoA-1 IgG levels at admission (p=0.01), but no difference for the 10-year global Framingham risk score (FRS) was observed (p=0.22). ROC analyses indicated that both MPO and anti-apoA-1 IgG were significant predictors of subsequent MACE (area under the curve [AUC]: 0.75, 95% confidence interval [95%CI]: 0.61–0.89, p=0.01; and 0.74, 95%CI: 0.59–90; p=0.01), but combining anti-apoA-1 IgG positivity and MPO>857 ng/ml displayed the best predictive accuracy (AUC: 0.78, 95%CI: 0.65–0.91; p=0.007). It was associated with a poorer MACE-free survival (98.2% vs. 57.1%; p<0.001, LogRank), with a positive likelihood ratio of 13.67, and provided incremental predictive ability over FRS. In conclusion, combining the assessment of anti-apoA-1 IgG and MPO appears as a promising risk stratification tool in patients with severe carotid stenosis.
Keywords: Autoantibodies; myeloperoxidase; atherosclerosis; major adverse cardiovascular events; carotid stenosis